PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN MATERI HUBUNGAN PROKLAMASI KEMERDEKAAN DENGAN UUD 1945 DALAM PEMBELAJARAN TATAP MUKA TERBATAS METODE PROBLEM SOLVING TERHADAP PESERTA DIDIK KELAS VIII - Mustakim Mustakim (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
in learning interactions between students and teachers because education is not only about acquiring or transforming knowledge but also about values, cooperation, and character. This pandemic situation is a challenge for the creativity of every teacher and educator in using technology to develop the world of education, especially in learning Pancasila and Citizenship Education. This research is a classroom action research (CAR) which aims to (1) see how the description of Pancasila and Citizenship Education learning in the material of the relationship between the Proclamation of Independence and the 1945 Constitution in face-to-face learning is limited through the application of Problem Solving learning and (2) Can Problem Solving learning be improve the learning outcomes of their Pancasila and civic education. The research subjects were 27 people consisting of 11 male students and 16 female students in class VIII UPTD SMP Negeri 28 Barru in the odd semester of the 2021/2022 academic year. The research instruments were observation sheets and learning outcomes tests. The data analysis technique used qualitative data analysis techniques. The results showed that the application of problem solving methods in limited face-to-face learning was proven to be able to improve learning outcomes of Pancasila and Citizenship Education on the material of the relationship between the Proclamation of Independence and the 1945 Constitution of the VIII grade students of UPTD SMP Negeri 28 Barru in the odd semester of the 2021/2022 academic year.